Some Ptychobothridaen tapeworm from freshwater fish Mastacembelus armatus at Aurangabad district (M.S.) India - Gedam1, Deepak Gaikwad3, Yogesh Reddy1, *Hemlata Wankhede2, Ajit (International Multidisciplinary Research Journal, 2011)
The present communication deals with description of some Ptychobothridaen tapeworm of the genus Circuomoncobothrium Shinde [17] viz Circumoncobothrium hemlatae n.sp and Circumoncobothrium shindei [21] from freshwater fish Mastacembelus armatus at Aurangabad district. Circumoncobothrium hemlatae n.sp it differs from all the known species of this genus scolex triangular, bothria sac like, matue segment twelve to thirteen time broader than long, testes 200 Ã¢â‚¬â€œ 225in number, ovary dumbbell shaped, vitellaria granular.Ã‚Â Circumoncobothrium shindei [21] is redescribed here; the present worm having some distinct character such as, in number of rostellar hooks and size of scolex.